A method for accounting for test fixture compliance when estimating proximal femur stiffness. Issue 13 (6th September 2016) - Rossman, Timothy; Dragomir-Daescu, Dan
Abstract: Fracture testing of cadaveric femora to obtain strength and stiffness information is an active area of research in developing tools for diagnostic prediction of bone strength. These measurements are often used in the estimation and validation of companion finite element models constructed from the femora CT scan data, therefore, the accuracy of the data is of paramount importance. However, experimental stiffness calculated from force–displacement data has largely been ignored by most researchers due to inherent error in the differential displacement measurement obtained when not accounting for testing apparatus compliance. However, having such information is necessary for validation of computational models. Even in the few cases when fixture compliance was considered the measurements showed large lab-to-lab variation due to lack of standardization in fixture design. We examined the compliance of our in-house designed cadaveric femur test fixture to determine the errors we could expect when calculating stiffness from the collected experimental force–displacement data and determined the stiffness of the test fixture to be more than 10 times the stiffness of the stiffest femur in a sample of 44 femora. When correcting the apparent femur stiffness derived from the original data, we found that the largest stiffness was underestimated by about 10%. The study confirmed that considering test fixture compliance is a necessary step in improving the accuracy of fracture test data for characterizing femur stiffness, and highlighted the need for test fixture design standardization for proximal femur fracture testing.